Peningkatan Kapabilitas Digital UMKM Makanan melalui Implementasi WhatsApp Business untuk Otomatisasi Layanan Pelanggan dan Pemesanan Produk di Desa Pemanggilan, Natar, Lampung Selatan - Ruswita, Istiana; Praptiwi, Riska Amalia (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
The advancement of digital technology provides opportunities for Micro, Small, and Medium Enterprises (UMKM) to improve customer service quality and business process efficiency. However, many food-based UMKM in Pemanggilan Village, Natar District, South Lampung Regency, still face limitations in utilizing digital technology to support marketing and product ordering activities. This community service program aimed to enhance the digital capabilities of UMKM owners through training and mentoring on the implementation of WhatsApp Business as a platform for customer service and product ordering. The methods employed included partner needs assessment, training on WhatsApp Business features, assistance in creating business profiles, configuring automated messages, developing product catalogs, and evaluating program outcomes through pre-tests and post-tests. The evaluation of 35 participants demonstrated a significant improvement in their knowledge and skills in using WhatsApp Business, with the average pre-test score increasing from 42.9 to 87.3 in the post-test, representing an improvement of 44.4 points. Participants were able to utilize business profiles, automated messaging, product catalogs, and order management features more effectively to support their business activities. The implementation of WhatsApp Business contributed to improving customer service responsiveness, facilitating business communication, and supporting the digital transformation of food-based UMKM in Pemanggilan Village. This program is expected to enhance the competitiveness and productivity of UMKM through the adoption of accessible and cost-effective digital technology.